23‐1: 5291 ppi Organic Light Emitting Diode Display using Field‐effect Transistors Including a C‐Axis Aligned Crystalline Oxide Semiconductor. Issue 1 (29th May 2019) - Katsui, Shuichi; Kobayashi, Hidetomo; Nakagawa, Takashi; Tamatsukuri, Yuki; Shishido, Hideaki; Uesaka, Shogo; Yamaoka, Ryohei; Nagata, Takaaki; Aoyama, Tomoya; Nei, Kosei; Okazaki, Yutaka; Ikeda, Takayuki; et al.
Abstract : C‐axis aligned crystalline oxide semiconductor field‐effect transistor (CAAC‐OS FET) can be scaled down to a width and length of 60 nm. We have fabricated an organic light‐emitting diode (OLED) display with more than 5000 ppi, which is required in virtual reality (VR) displays, by using CAAC‐OS FETs as the backplane.